DAMPAK PENCERAIAN ORANG TUA TERHADAP MOTIVASI BELAJAR ANAK DI DESA TADDAN TENGGAH KAB. SAMPANG - Rofi'ah, Rofi'ah Ofi; Misriyah, Misriyah; Andriyani, Nova; Nur Aini, Yuli (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
This research is motivated by the impact of parental divorce on children, resulting in the loss of important role models or examples for them. The psychological well-being of children is also disturbed, and they feel disappointed, which in turn affects their motivation to learn. The aim of this study is to investigate the impact of parental divorce on children's motivation to learn in Kampung Kebbun, Taddan Tenggah Village, Camplong District, Sampang Regency. The research method used is qualitative with a descriptive approach, and data collection techniques include observation, interviews, and documentation. Data analysis is conducted interactively. The results of this study, based on observations and interviews, show various impacts of parental divorce on children's motivation to learn. Some children who experience divorce still have high motivation to learn, although sometimes they experience unstable emotions and show independent traits. However, some children experience negative impacts such as decreased motivation to learn, lack of enthusiasm or laziness in learning, lack of concentration, lack of attention from parents leading to cessation of learning, uncontrollable emotions, and feelings of resentment. The conclusion of this study is that in Kampung Kebbun, Taddan Tenggah Village, Camplong District, Sampang Regency, the impact of parental divorce on children's motivation to learn includes decreased enthusiasm for learning, lack of enthusiasm in learning, and a tendency to become lazy in learning. As a recommendation, parents are advised to continue to provide adequate attention to their children, especially when they are studying, and to provide the necessary support and motivation to build their children's motivation to learn.